2011
DOI: 10.17221/180/2010-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Determination of fatty acid and tocopherol compositions and the oxidative stability of walnut (Juglans regia L.) cultivars grown in Serbia

Abstract: Rabrenovic B., Dimic E., Maksimovic M., Sobajic S.,Gajic-Krstajic L. (2011): Determination of fatty acid and tocopherol compositions and the oxidative stability of walnut (Juglans regia L.) cultivars grown in Serbia. Czech J. Food Sci., 29: 74-78.Five cultivars (Sampion, Jupiter, Sejnovo, Elit, and Geisenheim 139) of walnuts (Juglans regia L.) were collected during the 2008 harvest, from Cacak, Central Serbia. Two techniques of oil extraction were implemented -cold pressing and organic solvent extraction. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
23
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 16 publications
(9 reference statements)
10
23
1
Order By: Relevance
“…The total content of tocopherols in the analyzed samples ranged between 30.0 and 44.4 mg/100 g oil, which is comparable with other data published Demir and Cetin (1999), Savage et al (1999), Crews et al (2005). Rabrenovic et al (2011) reported total tocopherol in 5 walnut cultivars grown in Serbia was found between 28.4 and 42.4 mg/100 g. The highest content of total tocopherols was found in 'G-13' genotype fruit oil extracted by the Soxhlet method, while the lowest content was found in the 'G-6' genotype. The cultivar 'Sebin' had 36.9 mg/100 g total tocopherol in oil (Table 3).…”
Section: Tocopherolssupporting
confidence: 90%
See 1 more Smart Citation
“…The total content of tocopherols in the analyzed samples ranged between 30.0 and 44.4 mg/100 g oil, which is comparable with other data published Demir and Cetin (1999), Savage et al (1999), Crews et al (2005). Rabrenovic et al (2011) reported total tocopherol in 5 walnut cultivars grown in Serbia was found between 28.4 and 42.4 mg/100 g. The highest content of total tocopherols was found in 'G-13' genotype fruit oil extracted by the Soxhlet method, while the lowest content was found in the 'G-6' genotype. The cultivar 'Sebin' had 36.9 mg/100 g total tocopherol in oil (Table 3).…”
Section: Tocopherolssupporting
confidence: 90%
“…The cultivar 'Sebin' had 55.03%, 14.17%, 19.06% and 7.81% of linoleic, linolenic, oleic and palmitic acid content (Table 2). Rabrenovic et al (2011) revealed that predominant fatty acids in fruits of 5 walnut cultivars ('Sampion', 'Jupiter', 'Sejnovo', 'Elit', and 'Geisenheim 139') grown in Serbia were linoleic (57.2-65.1%), oleic (15.9-23.7%), linolenic (9.1-13.6%) and palmitic acid (6.3-7.7%). Ozrenk et al (2011) determined linoleic acid 50.58-66.60%, oleic acid 14.88-28.71% and linolenic acid 9.16-16.42% among walnut selections.…”
Section: Fatty Acid Contentmentioning
confidence: 99%
“…The tocopherol content in the present study was in accordance with that of walnut oil, in which the contents of total tocopherols and γ-tocopherol were 28.4-42.4 and 25.4-38.4 mg/100 g, respectively 27 .…”
Section: Physicochemical Characteristicssupporting
confidence: 86%
“…, and palmitic 6.3-7.7 acids, and the PUFAs, MUFAs and SFAs in walnut oil ranged in 67.4-75.7 , 15.9-23.9 and 8.3-9.4 , respectively 27 . Sielicka et al studied the compositions of non-refined flaxseed, walnut, rapeseed, pumpkin seed, evening primrose, and black cumin oils.…”
Section: Fatty Acid Compositionmentioning
confidence: 96%
“…In recent studies, it has been suggested that the ratio of oleic acid to linoleic acid could be used as a criterion for determining the almond kernel quality when evaluating oil stability and fatty acid composition [Kodad & The high rate of unsaturated fatty acids can also extend the shelf life of nuts, and has positive effects on human health [Rabrenovic et al, 2011]. Almond is also rich in unsaturated fatty acids [Abdallah et al, 1998;Sathe et al, 2008].…”
Section: Introductionmentioning
confidence: 99%